2000
DOI: 10.1071/ea98007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grazing management on phalaris herbage mass and persistence in summer-dry environments

Abstract: Grazing management strategies that included resting or intensely utilising pasture on a seasonal basis were compared for their effects on phalaris production and plant frequency (persistence). Experiments were established at 4 on-farm sites (Cootamundra ‘old’, Cootamundra ‘new’, Springhurst and Cavendish) in southern New South Wales and Victoria that had previously been sown to phalaris and were grazed by sheep. At each site, 8 core treatments and extra locally determined treatments were initially imposed in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 24 publications
1
4
1
Order By: Relevance
“…Preliminary results (Harris and Ayres 1997), at a high elevation site on the Northern Tablelands of New South Wales, showed good persistence of Australian phalaris under continuous grazing, despite severe drought in 1994-95. In contrast to the present experiments, similar studies in a southern, winter rainfall zone Virgona et al (2000) found that at 3 of the 4 sites studied, autumn-winter, rather than autumn-spring management was important for phalaris persistence.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Preliminary results (Harris and Ayres 1997), at a high elevation site on the Northern Tablelands of New South Wales, showed good persistence of Australian phalaris under continuous grazing, despite severe drought in 1994-95. In contrast to the present experiments, similar studies in a southern, winter rainfall zone Virgona et al (2000) found that at 3 of the 4 sites studied, autumn-winter, rather than autumn-spring management was important for phalaris persistence.…”
Section: Discussioncontrasting
confidence: 94%
“…Fertilised swards of Sirosa phalaris sown with a companion legume were studied at 3 sites on the North-West Slopes. Results of comparable TPSKP grazing management studies on Sirosa phalaris in predominantly winter rainfall zones of south-east Australia were reported by Virgona et al (2000).…”
Section: Introductionsupporting
confidence: 54%
“…If Holdfast GT survives equally as well as Australian, this experiment demonstrated it has production advantages in winter when feed is usually in short supply. If pastures can be managed through long‐term adherence to rotational stocking, destocking under very adverse conditions or tactical rests (Virgona et al ., ), then the winter‐active cultivars other than Holdfast GT (Holdfast, Sirosa, Landmaster, Advanced AT, Atlas PG) remain an equally or more productive option, and more productive in winter than Australian, and some will be preferable in moderately–strongly acidic soils (Advanced AT, Landmaster). Soil fertility strongly affected the ability of the phalaris stands to recover their basal frequency by vegetative expansion after the early decline due to overgrazing during drought.…”
Section: Resultsmentioning
confidence: 99%
“…Although rotationally stocked plots in this study were grazed to low residual mass in each grazing cycle, the high herbage mass achieved during the rest period clearly benefitted survival due probably to factors such as the development of larger phalaris plants, deeper roots and higher carbohydrate levels. These results confirm other reports of benefits from rotational stocking on phalaris composition and herbage mass (Virgona et al ., ; Warn and McLarty, ; Chapman et al ., ) and basal frequency (Culvenor, ). Studies have shown that tactical rests particularly in the autumn–winter winter period can also be effective in maintaining phalaris composition (Virgona et al ., ) and that flexibility in grazing interval is required to cope with varying seasonal conditions (Virgona and Bowcher, ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with normal Phalaris‐ based pasture systems that are subjected to periods of drought and where the main source of nitrogen is through symbiotic nitrogen fixation by clover, this experiment features a very high production rate. Virgona et al . (2000) reported spring pasture growth rates of up to 10 g/m 2 d −1 while Lolicato (2000) reported maximum spring growth rates of 15 g/m 2 d −1 for hybrid Phalaris.…”
Section: Discussionmentioning
confidence: 99%